2019
DOI: 10.3390/molecules25010035
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide@3D Hierarchical SnO2 Nanofiber/Nanosheets Nanocomposites for Highly Sensitive and Low-Temperature Formaldehyde Detection

Abstract: In this work, we reported a formaldehyde (HCHO) gas sensor with highly sensitive and selective gas-sensing performance at low operating temperature based on graphene oxide (GO)@SnO 2 nanofiber/nanosheets (NF/NSs) nanocomposites. Hierarchical SnO 2 NF/NSs coated with GO nanosheets showed enhanced sensing performance for HCHO gas, especially at low operating temperature. A series of characterization methods, including X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM), Transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Volatile organic compounds (VOCs) in residential buildings and in the workplace pose serious threats to public health [ 1 , 2 , 3 ]. As a typical colorless VOC, 2-butanone is produced industrially on a large scale, is widely used as a common solvent, denaturing agent and cleaning agent.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) in residential buildings and in the workplace pose serious threats to public health [ 1 , 2 , 3 ]. As a typical colorless VOC, 2-butanone is produced industrially on a large scale, is widely used as a common solvent, denaturing agent and cleaning agent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wan et al [ 78 ] reported a formaldehyde gas sensor with highly sensitive and selective gas sensing performances at low temperatures based on graphene oxide (GO)@SnO 2 nanofiber/nanosheets (NF/NSs) synthesized by electrospinning technique followed by a hydrothermal step ( Figure 5 l). Figure 5 m shows the XRD patterns of pristine SnO 2 NF/NSs, GO@SnO 2 NF/NSs nanocomposites and GO.…”
Section: Graphene Oxide-mos Gas Sensorsmentioning
confidence: 99%
“…Elsevier, 2019. ( l ) Sketch of the preparation process of GO@SnO 2 nanofiber (NF)/nanosheets (NSs) [ 78 ]. ( m ) XRD patterns of GO, SnO 2 NF/NSs and GO@SnO 2 NF/NSs nanocomposites with different GO concentrations [ 78 ].…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
See 2 more Smart Citations